Improving Student Performance in Introductory Accounting - Raising Minimum Grade Standards is Not the Answer - Phillips, Janet (The Accounting Educators' Journal, 2021)
An ongoing debate continues at universities surrounding whether or not to raise minimum grade standards. Because of an inherent risk that enrollments may decline as a result, it is important to examine whether minimum grade policies are associated with improved student performance. To address this issue, the current study examines the relationship between higher minimum grade requirements in introductory accounting and student grades. The new minimum grade requirement of â€œCâ€ was established beginning with the fall 2015 semester for introductory accounting to strengthen the quality of the program for an AACSB application. The research design included modeling introductory accounting grades over a ten-year period to examine any effect of the increase in the minimum grade on studentsâ€™ grades in the course. The multivariate regression equation considered variables previously found associated with introductory accounting grades (i.e., status as accounting major, grade point average, mathematics preparedness and previous experience taking the course). An additional dichotomous variable was introduced to capture the impact of students on the new program. All students were taught by the same professor, using the same textbook, teaching philosophy and examination format to enhance the comparison. Results suggest average grades in introductory accounting did not improve as expected.
Number: 1
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Number: 2
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found